17 fun food stories [videorecording (DVD)] (PBS Kids, 2024)
Enjoy delicious stories all about the different foods and sweet treats that favorite PBS Kids characters love! Alma tries to fix Mami's mofongo dish and Daniel Tiger makes pan pans at the Platypus house. Lyla and Luke enlist Stu to help make cupcakes, and Molly and Vera surprise Vera's mom with a traditional dish from the Philippines.